Pendampingan Penguatan Pendidikan Karakter di Sekolah Dasar Berorientasi Pelajar Pancasila - Zahra Khusnul Lathifah; R. Siti Pupu Fauziah; Abdul Kholik; Muhamad Aminulloh; Irma Inesia Sri Utami; Irwan Efendi; Gugun Gunadi (Warta LPM, 2022)
To realize a complete Indonesian human being, it is not enough only to have cognitive abilities, but also affective and psychomotor abilities. To become a person of character, students need to balance these three abilities. Strengthening character education in schools, according to Permendikbud No. 22 of 2020 is directed at the formation of a character- oriented to the Pancasila Student Profile. This service activity aims to provide knowledge and understanding to elementary school teachers as the frontline in supporting the Strengthening Character Education (PPK) program in schools, about character education oriented to the Pancasila Student Profile. The implementation method is carried out through five stages, namely: 1) planning; 2) organizing; 3) preparation for the implementation of activities; 4) implementation of activities and documentation; and 5) evaluation. The target of the activity in elementary school teachers in the Caringin District. The results obtained from the mentoring activities were: 1) increased understanding and knowledge of elementary school teachers about Pancasila Student-oriented character education by 8.04% based on the results of the pre-test and post-test; 2) the increasing commitment of teachers to implement the Pancasila Student- oriented character education program in an integrative and holistic way in classroom learning; and 3) the realization of positive synergy between local governments and universities in supporting the achievement of the 2022-2024 Ministry of Education and Culture Strategic Plan through Cooperation activities. The increased understanding and knowledge of teachers has not yet reached the expected target due to limited time for workshop activities. And as a follow-up plan, direct assistance will be carried out to participating teachers in their respective schools as a continuation scheme of the socialization stage at the time of the workshop.